PENGARUH PENGOLAHAN BAHAN BAKU TERHADAP KARAKTERISTIK TABEL MANDO IKAN TONGKOL (Euthynnus affinis) - Anggi Rananda; Jumsurizal Jumsurizal; R Marwita Sari Putri (Fisheries Product Technology Department, Faculty of Marine Science and Fisheries, Universitas Maritim Raja Ali Haji, 2023)
The abundance of fish in Natuna waters, especially tuna, so that many food products are produced such as crackers, kernas and mando tables. Mando table is a typical Natuna food made from smoked tuna and sago flour which is then mixed with grated coconut and other spices, boiled tuna, steamed tuna and fried tuna. The process of making mando tables includes preparation of raw materials, determination of mando table formulations, manufacture of mando tables, organoleptic testing, proximate testing and TPA (Texture Profile Analysis). The testing parameters of this research include organoleptic test, proximate testing and TPA (Texture Profile Analysis). From the results of the study from the Mando table, it can be used for organoleptic testing at T1 (30% smoked fish and 26% sago flour) has a yellow brown color, at T1 it has a stronger fish aroma, for T2 it has a savory taste and sufficient fish taste and T2 It has a dense and compact texture. The proximate test results in the Mando T1 table have the best treatment with parameters water content 33.24%, ash content 1.067%, fat content 13.189%, protein content 0.72% and carbohydrate content 50.884%. The results of the TPA (Texture Profile Analysis) test are the best values ??for hardness 2.820%, springiness 64.67%, cohesiviness 0.28% and adhesiveness 51.59% in T1 treatment.